Pelvic Lymphadenectomy in Vulvar Cancer – Does it make sense? - Woelber, Linn; Bommert, Mareike; Prieske, Katharina; Fischer, Inger; Zu Eulenburg, Christine; Vettorazzi, Eik; Harter, Philipp; Jueckstock, Julia; Hilpert, Felix; De Gregorio, Niko; Iborra, Severine; Sehouli, Jalid; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Since the publication of the updated German guideline in 2015, the recommendations for performing pelvic lymphadenectomy (LAE) in patients with vulvar cancer (VSCC) have changed considerably. The guideline recommends surgical lymph node staging in all patients with a higher risk of pelvic lymph node involvement. However, the current data do not allow the population at risk to be clearly defined, therefore, the indication for pelvic lymphadenectomy is still not clear. There are currently two published German patient populations who had pelvic LAE which can be used to investigate both the prognostic effect of histologically verified pelvic lymph node metastasis and the relation between inguinal and pelvic lymph node involvement. A total of 1618 patients with primary FIGO stage ≥ IB VSCC were included in the multicenter AGO CaRE-1 study (1998-2008), 70 of whom underwent pelvic LAE. During a retrospective single-center evaluation carried out at the University Medical Center Hamburg-Eppendorf (UKE), a total of 514 patients with primary VSCC treated between 1996-2018 were evaluated, 21 of whom underwent pelvic LAE. In both cohorts, around 80% of the patients who underwent pelvic LAE were inguinally node-positive, with a median number of three affected groin lymph nodes. There were no cases of pelvic lymph node metastasis without inguinal lymph node metastasis in either of the two cohorts. Between 33-35% of the inguinal node-positive patients also had pelvic lymph node metastasis; the median number of affected groin lymph nodes in these patients was high (> 4), and the maximum median diameter of the largest inguinal metastasis was > 40 mm in both cohorts. Pelvic lymph node staging and pelvic radiotherapy is therefore probably not necessary for the majority of node-positive patients with VSCC, as the relevant risk of pelvic lymph node involvement was primarily found in node-positive patients with high-grade disease. More, ideally prospective data collections are necessary to validate the relation between inguinal and pelvic lymph node involvement.
CRIS-Team Scopus Importer:2020-12-25
Keywords: lymph node metastasis; pelvic lymphadenectomy; prognosis; recurrence; vulvar cancer